Effects of attenuation and dispersion factors on Tebuthiuron leaching simulation. - SPADOTTO, C. A. (2007)
Differences on response of mathematical models on herbicide leaching in the environment can occur due to the models and their limitations, mainly when using soil lysimeters. Tebuthiuron is a herbicide used in sugarcane crop and is applied in the recharge area of the Guarany aquifer in Brazil, one of the largest in the world. This study was conducted to compare the leaching potential of the herbicide within lysimeters using sandy soils of the Espraiado watershed in the recharge area from the region of Ribeirão Preto, SP, Brazil. The traditional Attenuation Factor (AF) model was used at various soil layers, adding a Dispersion Factor (DF) to the model. The fitness of the model was good for the total amount of tebuthiuron leached, but not for the rate of leaching. The model overestimated the level of herbicide leaching at 100 days after application, but the final concentration leached with the water was as predicted by the model.